A Fruit Fly, Anastrepha ocresia (Walker) (Insecta: Diptera: Tephritide) - Howard V. Weems (EDIS)
This small, orange-brown fly with patterned wings, a banded abdomen, and a somewhat long ovipositor sheath, is one of six species of fruit flies of the genus Anastrepha that occur in Florida, or which have been established in Florida at some time. There is a distinct possibility that this species has not survived in Florida. This revised 2-page fact sheet was written by H. V. Weems, Jr. and published by the UF Department of Entomology and Nematology, March 2012.